Peningkatan Kualitas Air di SDI As Salam Malang: Sistem Filtrasi Berlapis untuk Mengatasi Kontaminasi Besi Tinggi - Putu Hadi Setyarini; Sisca Fajriani; Evi Nur Cahya; Mochammad Roviq; Nuretha Hevy Purwaningtyas (Jurnal Surya Masyarakat, 2025)
The quality of water used in daily activities plays a crucial role in supporting health, comfort, and safety, particularly in educational environments. At SDI As Salam, Malang City, groundwater utilized by the school contained very high concentrations of iron (Fe), resulting in a a yellowish color, unpleasant odor, and suspended particles that reduce clarity due to oxidation of dissolved iron into brown or yellow solids, thereby significantly lowering water quality and posing health risks for students who consume it daily. To address this issue, the Doktor Mengabdi Team from Universitas Brawijaya implemented a multi-layer filtration system using affordable local materials such as silica sand, activated carbon, zeolite, and manganese greensand, designed to remove contaminants including dissolved iron, heavy metals, and harmful chemicals. The results showed that iron concentration decreased by more than 80%, turbidity reduced from 30 NTU to 2 NTU, and pH increased from 5.8 to 6.8, while microbiological testing confirmed a significant reduction in E. coli and total coliform, indicating that the filtered water is safe for use. Thus, the application of this multi-layer filtration system not only improves water quality but also creates a healthier environment that supports more effective learning activities.